Remarks relevant to classical maximum principles - Cristian-Paul Danet (Journal of Applied Mathematics)
We extend, sharpen, or give independent proofs of classical maximum principles. We also concentrate on maximum principles for equations of higher order. All proofs (except for one) are derived via comparison principles. The two parts maybe read independently, but the whole paper is not self-contained.